Model of Medical and Psychological Rehabilitation for Post-COVID Syndrome: Evaluating the Effectiveness of a Remote Interaction Program During Wartime - Burdeinyi, Андрій (Psychosomatic Medicine and General Practice, 2025)
Relevance. The widespread occurrence of post-COVID syndrome is often accompanied by psychological issues such as anxiety, depression, and post-traumatic stress disorder (PTSD). The ongoing military conflict in Ukraine exacerbates these symptoms, further complicating the emotional and psychological state of patients. Effective methods of medical and psychological rehabilitation have become critical in mitigating the negative impact of stress and the somatic symptoms associated with post-COVID syndrome in a persistent stressful environment. Given the limited access to in-person medical services, remote rehabilitation serves as an effective tool for providing patient support. The implementation of a remote medical and psychological rehabilitation program focused on stabilizing mental health not only improves the quality of life for participants but also contributes to the prevention of anxiety, depression, and post-traumatic states. This is especially vital for adapting to everyday life and restoring health amid the war and its consequences. Aim. To assess the predictive effectiveness of a medical and psychological rehabilitation program conducted via remote interaction for patients with anxiety and depressive post-COVID disorders. Materials and Methods. On the 153rd day of the study, 240 participants were evaluated. They had been previously randomized into the study group (n=122) and the comparison group (n=118) with anxiety and depressive post-COVID disorders. Anxiety symptoms were assessed using the Generalized Anxiety Disorder Scale (GAD-7), and depression was evaluated using the Patient Health Questionnaire-9 (PHQ-9). The Somatic Symptom Scale-8 (SSS-8) was used to assess the intensity of somatic symptoms. PTSD symptoms were measured using the PTSD Checklist for DSM-5 (PCL-5), and quality of life was evaluated using Chaban’s Quality of Life Scale (CQLS). Assessments were conducted on the first day of the study (Day 1), the last day of the rehabilitation program (Day 63), and three months after the completion of the intervention protocol (Day 153). Results. Participants in the study group demonstrated a significant reduction in anxiety and depression levels as measured by the GAD-7 and PHQ-9 scales. Minimal anxiety was observed in 92.6% of participants, while 51.7% of the comparison group experienced severe anxiety (p<0.001). Regarding depression, 84.3% of the study group had minimal symptoms, while 37.3% of the comparison group experienced severe depression. Additionally, the intensity of somatic symptoms decreased significantly over three months: 91.0% of the study group reported minimal symptom levels, while 39.0% of the comparison group had moderate and 37.3% had high symptom intensity (p<0.001). The study also revealed a substantial reduction in PTSD symptoms: after three months, none of the participants in the study group exhibited clinically significant symptoms, whereas the number of participants in the comparison group with PTSD symptoms increased from 44 to 47 (p<0.001). Quality of life assessments using the CQLS indicated that 73.8% of the study group reached a very high level of quality of life compared to only 6.8% of the comparison group, where 39.8% had a very low quality of life (p<0.001). These findings highlight the effectiveness of the rehabilitation program in improving the psychological, emotional, and social functioning of participants.